Generation and characterization of a tamoxifen-inducible lineage tracing tool Cd2-P2A-CreERT2 knock-in mice - Guo, Yang; Zhu, Mengyan; Yu, Zhilan; Li, Qing; Chen, Yanjuan; Ci, Lei; Sun, Ruilin; Shen, Ruling (Frontiers in Immunology, 2025)
IntroductionThe new targeted gene editing technologies, such as the CRISPR/Cas system, enable researchers to insert or delete genes at targeted loci efficiently. The Cre-loxp recombination system is widely used to activate or inactivate genes with high spatial and temporal specificity.MethodsUsing the CRISPR/Cas9 system, we inserted the CreERT2 transgene expression cassette into the Cd2 gene locus to generate conditional Cre-driver line Cd2-CreERT2 knock-in mice, which drove the expression of CreERT2 by the endogenous Cd2 promoter. By mating the Cd2-CreERT2 strain with a Rosa26-LSL-tdTomato reporter mouse strain which contains a tdTomato expression fragment blocked with a loxP-flanked STOP cassette (LSL) driven by a CAG promoter, a Cd2-CreERT2;Rosa26-LSL-tdTomato reporter strain was obtained to evaluate the expression pattern of CD2 in different cell types.ResultsAfter treatment with tamoxifen, the Cd2-CreERT2 knock-in mice were induced to perform efficient recombination at the loxP site following CreERT2 activation and cause the expression of tdTomato fluorescence. The tdTomato and CD2 were expressed in the T cells of peripheral blood, spleen and mesenteric lymph nodes, whereas detected in a low proportion in the B cells. While about 20% of cells labeled with tamoxifen-induced tdTomato were CD2+ monocytes in peripheral blood, 10% of dendritic cells were tdTomato+/CD2+ cells. Tamoxifen-independent expression of tdTomato occurred in approximately 3% of CD2+ macrophages, but in negligible (~0.5%) in CD2+ granulocytes.DiscussionThis work supplied a new transgenic mouse as a valuable tool for lineage tracing in CD2-expressing cells, for conditional mutant studies of immune modulatory effects in a time-dependent manner, and analysis of the potential therapeutic effect of CD2-targeting biologics.